2009
DOI: 10.2519/jospt.2009.2988
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effect of Orthotic Management on Grip Strength of Patients With Lateral Epicondylosis

Abstract: The (A) placebo, (B) counterforce elbow strap, (C) counterforce elbow sleeve, and (D) wrist splint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 25 publications
2
40
1
4
Order By: Relevance
“…Overall, despite variations in study designs, timing of outcomes, type of brace, and comparator groups, 5 most studies have shown that elbow or forearm braces improve pain and function in people with lateral epicondylalgia. 2,13,18,32 Although the results of our study found an improvement between prebracing and postbracing measures, overall, the brace conditions were no more effective than the control at improving immediate outcomes. As such, it appears that the additional strap on the forearm-elbow brace does not improve the efficacy of the existing forearm brace to immediately relieve pain or improve function.…”
Section: Discussioncontrasting
confidence: 45%
“…Overall, despite variations in study designs, timing of outcomes, type of brace, and comparator groups, 5 most studies have shown that elbow or forearm braces improve pain and function in people with lateral epicondylalgia. 2,13,18,32 Although the results of our study found an improvement between prebracing and postbracing measures, overall, the brace conditions were no more effective than the control at improving immediate outcomes. As such, it appears that the additional strap on the forearm-elbow brace does not improve the efficacy of the existing forearm brace to immediately relieve pain or improve function.…”
Section: Discussioncontrasting
confidence: 45%
“…18,[167][168][169][170][172][173][174][175][176][177][178][179][180][181][182][183][184][185][188][189][190][191][192][193][194][195][196][197][198] The majority of studies had small sample sizes (≤ 50 participants, n = 18; 51-100 participants, n = 15; > 100 participants, n = 3).…”
Section: Randomised Controlled Trials Not Included In An Existing Sysmentioning
confidence: 99%
“…Most typically, the primary pathology in tendinosis of the extensor carpi radialis brevis (ECRB) tendon 1-2 cm dista to its attachment on the lateral epicondyle [Altan, 2008;Jafarian, 2009]. In general, microscopic evaluation of the tendons does not show signs of inflammation, but rather angiofibroblastic degeneration and collagen disarray.…”
Section: Introductionmentioning
confidence: 99%